Speckle-tracking echocardiography for predicting improvement of myocardial contractile function after revascularization: a meta-analysis of prospective trials - Ballo Haitham; Doghman Fatma; Hartikainen Juha; Saraste Antti; Knuuti Juhani (SPRINGER, 2025)
Some studies have indicated that the use of 2D-Speckle tracking echocardiography (2DSTE) aids in predicting recovery of myocardial contractile function after revascularization in patients with chronic ischemic left ventricular (LV) dysfunction or acute myocardial infarction (MI). The purpose of this meta-analysis was to evaluate the diagnostic accuracy of 2DSTE strain in the detection of myocardial viability at rest and during low-dose dobutamine (LDD) stress. A systematic review for all prospective trials using 2DSTE to assess myocardial viability until January 2019 was done. Using a standard approach of meta-analysis for diagnostic tests. Overall, nine studies including 525 patients with either chronic ischemic heart disease or acute MI fulfilled the inclusion criteria. Seven studies used longitudinal strain (LS) at rest, nine studies used circumferential strain (CS) at rest, four studies used LS during LDD stress, and four studies used CS during LDD stress. LS and CS during LDD stress showed equally high sensitivity (81.5% and 81.5% respectively) and specificity (81.3% and 81.4% respectively) for detecting reversible dysfunction. At rest, LS and CS showed equally lower sensitivity (67.1%, p < 0.0001 vs. LDD stress and 68.7%, p < 0.0001, vs. LDD stress, respectively) and specificity (64%, p < 0.0001 vs. LDD stress and 65.7%, p = 0.0008 vs. LDD stress, respectively) as compared with LDD stress. LS and CS by 2DSTE during LDD stress accurately identify reversible ischemic myocardial dysfunction in patients with chronic ischemic LV dysfunction or after MI. The use of LDD stress can be recommended over resting strain measures in this setting.